INVESTIGATING STUDENTS’ ABILITY IN ANALYZING COMPLEX PROCEDURAL TEXT USING THE PROBING PROMPTING LEARNING MODEL - Feronika Patroli; Elvie A. Sepang; Thelma I. M. Wengkang (SoCul: International Journal of Research in Social Cultural Issues, 2023)
This study aims at exploring the ability of the 7th grade students in analyzing structure of complex procedure text using probing prompting learning model approach. This descriptive study was carried out at SMP Negeri 12 Manado located in Bunaken, Manado city. 20 7th grade students were the object of this study. The research was conducted from October to November in 2021 academic year. Data collection techniques involved observation and tests, while data analysis used the percentage formula. The results showed that students' ability to analyze the structure of complex procedural texts, especially on the topic "How to plant flowers," was categorized as proficient with a class average score of 82.5%, exceeding the 80% limit. In detail, the average score of students in the title section is 82.5%, which is also classified as proficient. While in the objective section, the average score was 73.33%, which can be classified as moderately capable. The tools and materials section received an average score of 98.33%, which is included in the excelent category. Then, in the steps section, the average score was 78.75%, which falls into the moderately capable category. Finally, in the closing section, students achieved an average score of 85%, which is also classified as proficient.